Impact of Human Immunological Responses and Viral Genetic Diversity on Outbreak of Human Monkeypox Virus. A Comprehensive Literature Review Study: Impact of Immunity and Genetic Diversity on Monkeypox - Shabbir, Irsa; Habib, Faiza; Habib, Muhammad Umar; Qader, Abdul; Habib, Aamna; Rafique, Sadia (Pakistan Journal of Health Sciences, 2024)
Monkeypox was caused by Monkeypox Virus (MPXV) and can infect both humans and animals. An understanding of the interplay between host immunity and genetic diversity was necessary to understand the etiology and epidemiology of monkeypox disease. Objective: To clarify how genetic differences and host immune responses interact when a moneypox infection occurs. Furthermore, we also aim to provide insights into individual variability in illness outcomes and possible treatment targets by investigating how distinct genetic profiles affect immune system activation and efficacy. Methods: Recent research on monkeypox, concentrating on the immune response mechanisms of the host and genetic variables linked to virus vulnerability have thoroughly analyzed. For this purpose, the data were searched from various research engines such as google scholar, pubmed, medline etc., by using different key words i.e., monkeypox and host immunity, monkeypox and antibodies interactions, monkeypox outbreak, mnkeypox strains. Conclusions: The way a monkeypox infection progresses and turns out was greatly influenced by the interplay between host genetic differences and immunological responses. Public health initiatives and the creation of tailored treatment plans can both benefit from the identification of genetic markers linked to immunological response profiles and vulnerability.